2009
DOI: 10.3810/hp.2009.12.269
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hypothermia Induced within 10 Hours After Birth Improved Neurological Outcome in Newborns with Hypoxic-Ischemic Encephalopathy

Abstract: Systemic hypothermia reduced the risk of disability in infants with moderate HIE, in accordance with earlier studies. Hypothermia was induced within 6 hours in most infants, but delaying the onset to 6 to 10 hours after birth did not negatively affect primary outcome. Further studies with a large number of patients are needed to confirm that delayed cooling is equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…7 A number of smaller studies reported data consistent with the large pragmatic trials. 17-22 Preliminary information from the Cool Cap trial shows favorable outcome in survivors of HIE at 18 months is highly associated with favorable functional outcome at 7-8 years. 23 The NICHD Whole Body Cooling trial shows that the beneficial effects of hypothermia for neonatal HIE noted at 18 months persist to childhood.…”
Section: Clinical Trials Of Hypothermic Neural Rescuementioning
confidence: 99%
See 1 more Smart Citation
“…7 A number of smaller studies reported data consistent with the large pragmatic trials. 17-22 Preliminary information from the Cool Cap trial shows favorable outcome in survivors of HIE at 18 months is highly associated with favorable functional outcome at 7-8 years. 23 The NICHD Whole Body Cooling trial shows that the beneficial effects of hypothermia for neonatal HIE noted at 18 months persist to childhood.…”
Section: Clinical Trials Of Hypothermic Neural Rescuementioning
confidence: 99%
“…4142 There are recent report indicating a significant portion of infants (13 and 18%) cooled beyond the 6 hour of age tested i the randomized trials 43,44 and limited data supporting the potential benefit from such delayecoling. 22 …”
Section: Further Research Into Hypothermic Neural Rescuementioning
confidence: 99%
“…Extensive experimental and clinical research has been carried out into prolonged moderate hypothermia for perinatal asphyxial encephalopathy [2][9]. Synthesis of the results of randomised controlled trials show that the number needed to treat (NNT) with cooling to prevent one additional death or disabled survivor is 7, 95% confidence interval (CI) 4–14.…”
Section: Introductionmentioning
confidence: 99%
“…A significant breakthrough was that post-insult hypothermia within 6 hours reduced severe disability, including cerebral palsy [2]. Other milestones in the field were the findings that low dose rhEPO treatment [3] or delayed hypothermia up to 10 hours [4] reduce the risk of disability in infants with moderate term hypoxic-ischemic encephalopathy. Current therapeutic options for preterm hypoxic-ischemic brain injury are limited and predominantly supportive, to maintain physiological parameters.…”
Section: Introductionmentioning
confidence: 99%